Decolonial identities in the leadership coaching space: against neoliberal leader identity regulation - Seyama-Mokhaneli, Sadi; Belang, Thato (Frontiers in Psychology, 2024)
The study uses the decolonial lens to disrupt the contentious dominance of whiteness in leadership development, not to mention in coaching, in management and organization studies (MOS). It contributes insights into how a decolonizing coaching space enables and guides a coachee to reflect and rethink the navigation of the realities of her decolonial identity. The decolonial identity encapsulates the authentic self and the neoliberal identity is the plastic self in a neoliberal university context. Universities' pervasive and normalized neoliberal discourse has become a “paradigm”—the overarching worldview through which universities' visions, missions, strategic objectives, and values are constructed. For academics to thrive in their performance and “walk on water” in achieving performance targets, they ought to embrace being academic capitalists, which shapes idealized neoliberal identities—conforming identities, complicit in undermining social, economic, and epistemic justice. Qualitative research methods were utilized to conduct a reflexive study, and data collected from the reflections and reflexive dialogues in leadership development coaching sessions and journals were thematically analyzed. The study reveals that the coach and coachee's shared decolonial identity offered counter-narratives that unmask the dominant great “white” man leadership in organizations. It also illuminates insights into the significance of black feminist pedagogy in the coaching process to honor the coachee's decolonial identity and rich cultural experiences. It enabled her to explore them critically and derive meanings from developing decolonizing, critically conscious leadership strategies for emerging transformation challenges. Meaningful dialogue dimensions emerged, which served as lenses that steered a decolonial approach in supporting the coachee to reflect and rethink the leadership performance vision, strategic objectives, action plans, implementation, and monitoring.